RADIONUCLIDE SCANNING WITH I-123 IN GRAVES DISEASE - Vedayanti, Putu Diah; Astuti, Lisna; Martadiani, Elisanti Dwi (E-Jurnal Medika Udayana; vol 3 no 1 (2014):e-jurnal medika udayana)
Graves’ disease is the most common form of thyrotoxicosis which caused by autoimmune that attacks the thyroid gland. This disease will lead such following syndromes: thyrotoxicosis, goiter, ophthalmopathy, dermopathy. The sensitive TSH assay is the single best screening test for hyperthyroidism, and in most outpatient clinical situations. But when there is a doubt to distinguish diffuse toxic goiter (Graves’ disease) from autonomous toxic nodule (Plummer’s disease), radioinuclide scanning can be performed. I-123 is one of the preferable radiosisotope because it can produce clear image and short enough half-life, although the price is expensive.
Keywords: radioisotope scanning, graves’ disease, Iodine-123